TH1.2: Exploring Gendered Entry Points in the Goat Value Chain in Senegal - Faas, Simone; Kane, Papa Abdoulaye; Barry, Mamadou Bobo; Tall, Thiane; Ringler, Claudia; Bryan, Elizabeth (International Food Policy Research Institute, 2022)
The goat value chain (VC) plays an important role in household economics and diets throughout Sub-Saharan Africa, particularly in Senegal. The resilience of goat production in unpredictable climates suggests the potential for increased importance as climate change effects become more disruptive to traditional food systems and diets. The primary research question of this study is: What is the role of goats and the goat VC for climate resilience, women's empowerment and improved nutrition in Senegal? By conducting interviews and focus group discussions (FGDs) with goat VC actors in urban/peri-urban, agricultural, and pastoralist areas of Senegal, this study seeks to identify potential entry points for interventions along the VC, especially for women. In June and July 2022, in collaboration with the IFPRI Gender, Climate Change and Nutrition Integration Initiative, researchers from the Institut Sénégalais de Recherche Agricole (ISRA) facilitated 12 FGDs, six with men and six with women, across two regions, Niakhar and Louga, and conducted 30 key informant interviews with various goat VC actors in the regions of Dakar, Niakhar, and Louga. Preliminary results indicate that more women are becoming engaged in goat rearing and production, becoming owners of the goats they manage and controlling the goat-related incomes. Women have developed climate resilient strategies, including storing foraging materials during winter and selling goats to purchase food during the hunger season. Supported by USAID, the findings of this study will inform future interventions that aim to enhance women's engagement in the goat VC, improve household nutrition, and increase women's empowerment.